Innovative Data Collecting System of Services Provided by Medical Laboratories - Migodzinski, A.; Ritter, R.; Kaminski, M.; Chlapinski, J.; Sakowicz, B. (ХНУРЭ, 2011)
The article presents features of an innovative system that provides data collection of services provided by medical laboratories. System has been developed based on Java Enterprise Edition platform with usage of Spring and Hibernate frameworks combined with jQuery library.
Keywords: Java EE; Java; hibernate; spring framework